Blockade of P2X4 Receptors Inhibits Neuropathic Pain-Related Behavior by Preventing MMP-9 Activation and, Consequently, Pronociceptive Interleukin Release in a Rat Model - Jurga, Agnieszka M.; Piotrowska, Anna; Makuch, Wioletta; Przewlocka, Barbara; Mika, Joanna (Frontiers in Pharmacology, 2017)
Neuropathic pain is still an extremely important problem in today’s medicine because opioids, which are commonly used to reduce pain, have limited efficacy in this type of pathology. Therefore, complementary therapy is needed. Our experiments were performed in rats to evaluate the contribution of the purinergic system, especially P2X4 receptor (P2X4R), in the modulation of glia activation and, consequently, the levels of nociceptive interleukins after chronic constriction injury (CCI) of the right sciatic nerve, a rat model of neuropathic pain. Moreover, we studied how intrathecal (ith.) injection of a P2X4R antagonist Tricarbonyldichlororuthenium (II) dimer (CORM-2) modulates nociceptive transmission and opioid effectiveness in the CCI model. Our results demonstrate that repeated ith. administration of CORM-2 once daily [20 µg/5 µl, 16 h and 1 h before CCI and then daily] for 8 consecutive days significantly reduced pain-related behavior and activation of both spinal microglia and/or astroglia induced by CCI. Moreover, even a single administration of CORM-2 on day 7 after CCI attenuated mechanical and thermal hypersensitivity as efficiently as morphine and buprenorphine. In addition, using Western blot, we have shown that repeated ith. administration of CORM-2 lowers the CCI-elevated level of MMP-9 and pronociceptive interleukins (IL-1β, IL-18, IL-6) in the dorsal L4-L6 spinal cord and/or DRG. Furthermore, in parallel, CORM-2 upregulates spinal IL-1Ra; however, it does not influence other antinociceptive factors, IL-10 and IL-18BP. Additionally, based on our biochemical results, we hypothesize that p38MAPK, ERK1/2 and PI3K/Akt but not the NLRP3/Caspase-1 pathway are partly involved in the CORM-2 analgesic effects in rat neuropathic pain. Our data provide new evidence that P2X4R may indeed play a significant role in neuropathic pain development by modulating neuroimmune interactions in the spinal cord and DRG, suggesting that its blockade may have potential therapeutic utility.